Microbe-mediated intestinal NOD2 stimulation improves linear growth of undernourished infant mice - Schwarzer, Martin; Gautam, Umesh Kumar; Makki, Kassem; Lambert, Anne; Brabec, Tomáš; Joly, Amélie; Šrůtková, Dagmar; Poinsot, Pierre; Novotná, Tereza; Geoffroy, Stéphanie; Courtin, Pascal; Hermanová, Petra Petr; et al. (Science (New York, N.Y.), 2023)
The intestinal microbiota is known to influence postnatal growth. We previously found that a strain of Lactiplantibacillus plantarum (strain LpWJL) buffers the adverse effects of chronic undernutrition on the growth of juvenile germ-free mice. Here, we report that LpWJL sustains the postnatal growth of malnourished conventional animals and supports both insulin-like growth factor-1 (IGF-1) and insulin production and activity. We have identified cell walls isolated from LpWJL, as well as muramyl dipeptide and mifamurtide, as sufficient cues to stimulate animal growth despite undernutrition. Further, we found that NOD2 is necessary in intestinal epithelial cells for LpWJL-mediated IGF-1 production and for postnatal growth promotion in malnourished conventional animals. These findings indicate that, coupled with renutrition, bacteria cell walls or purified NOD2 ligands have the potential to alleviate stunting.
Keywords: gnotobiologické modely; Insulin; střeva; Nod2 Signaling Adaptor Protein; inzulin; epitelové buňky; Germ-Free Life; Epithelial Cells; Insulin-Like Growth Factor I; střevní sliznice; Gastrointestinal Microbiome; Growth Disorders; poruchy růstu; střevní mikroflóra; insulinu podobný růstový faktor I; Lactobacillaceae; buněčná stěna; Animals; Cell Wall; Malnutrition; Acetylmuramyl-Alanyl-Isoglutamine; zvířata; Intestinal Mucosa; myši; acetylmuramyl-alanyl-isoglutamin; podvýživa; růst; Growth; Intestines; Mice; signální adaptorový protein Nod2